Health Literacy, Cognitive Function, Proper Use, and Adherence to Inhaled Asthma Controller Medications Among Older Adults With Asthma - O’Conor, Rachel (Chest, 2015)
BACKGROUND: We sought to investigate the degree to which cognitive skills explain associations between health literacy and asthma-related medication use among older adults with asthma. METHODS: Patients aged ≥ 60 years receiving care at eight outpatient clinics (primary care, geriatrics, pulmonology, allergy, and immunology) in New York, New York, and Chicago, Illinois, were recruited to participate in structured, in-person interviews as part of the Asthma Beliefs and Literacy in the Elderly (ABLE) study (n = 425). Behaviors related to medication use were investigated, including adherence to prescribed regimens, metered-dose inhaler (MDI) technique, and dry powder inhaler (DPI) technique. Health literacy was measured using the Short Test of Functional Health Literacy in Adults. Cognitive function was assessed in terms of fluid (working memory, processing speed, executive function) and crystallized (verbal) ability. RESULTS: The mean age of participants was 68 years; 40% were Hispanic and 30% non-Hispanic black. More than one-third (38%) were adherent to their controller medication, 53% demonstrated proper DPI technique, and 38% demonstrated correct MDI technique. In multivariable analyses, limited literacy was associated with poorer adherence to controller medication (OR, 2.3; 95% CI, 1.29-4.08) and incorrect DPI (OR, 3.51; 95% CI, 1.81-6.83) and MDI (OR, 1.64; 95% CI, 1.01-2.65) techniques. Fluid and crystallized abilities were independently associated with medication behaviors. However, when fluid abilities were added to the model, literacy associations were reduced. CONCLUSIONS: Among older patients with asthma, interventions to promote proper medication use should simplify tasks and patient roles to overcome cognitive load and suboptimal performance in self-care.